2015
DOI: 10.4103/0019-5278.173998
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and health-related quality of life among public sector bank employees: A cross-sectional study in Mysore, Karnataka, India

Abstract: Background:Occupational morbidities have been estimated to cause an economic loss up to 10–20% of the gross national product of a country. It is an important cause of occupational morbidity and decreased quality of life (QOL) for the workers.Aim:The aim of the present study is to assess the level of occupational stress and its association with the QOL among the public sector bank employees.Materials and Methods:The present study was conducted among employees of public sector banks in Mysore district, Karnataka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…They work a highly stressful and demanding profession which is not very well rewarded, as reported in several studies [ 38 , 39 , 40 , 41 ]. The auxiliary personnel (although they were low in number in our study) seem to have the worst health status and poorer HRQoL compared to other studies [ 42 , 43 , 44 ]. We reported the lowest scores on all SF-36 dimensions, apart from that of mental health where nurses scored worse.…”
Section: Discussioncontrasting
confidence: 80%
“…They work a highly stressful and demanding profession which is not very well rewarded, as reported in several studies [ 38 , 39 , 40 , 41 ]. The auxiliary personnel (although they were low in number in our study) seem to have the worst health status and poorer HRQoL compared to other studies [ 42 , 43 , 44 ]. We reported the lowest scores on all SF-36 dimensions, apart from that of mental health where nurses scored worse.…”
Section: Discussioncontrasting
confidence: 80%
“…Second, the particular stressors characteristic of the sample's financial industry setting (Malamardi et al, 2015) may have also influenced the findings; however, this was not explored in this study. To be sure, bank employees may feel unique pressures; moreover, their quality of life is often negatively affected by occupational stress.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 97%
“…Zhang Ying’s research examined occupational stress and found that higher levels of stress among medical staff led to poorer quality of life, and occupational stress is an important factor affecting the quality of life of medical staff [29]. A study carried out by Malamardi showed that occupational stress is associated with quality of life in the banking sector, and that interventions are required to mitigate the occupational stress experienced by employees [30].…”
Section: Introductionmentioning
confidence: 99%